Average magnesite composition from selected serpentinite and listvenite samples from hole BT1B, Oman Drilling Project - Andreas Beinlich; Oliver Plümper; Esmée Boter; Inigo A Müller; Fatma Kourim; Martin Ziegler; Yumiko Harigane; Peter B Kelemen; The Oman Drilling Project Phase 1 Science Team (PANGAEA, 2020)
The presented carbonate electron microprobe data were derived from representative carbonate-bearing serpentinite and listvenite samples in Hole BT1B, OmanDP. The analyzed carbonate grains are chemically zoned and the data represents averages for compositionally and texturally comparable zones, e.g. matrix magnesite in 44-03 is always the core as the rim is dolomite. Electron microprobe analysis was conducted using the JEOL 8530F FE electron microprobe at Centre for Microscopy, Characterization and Analysis (CMCA), The University of Western Australia, using an acceleration voltage of 15 keV and a 5 μm defocused beam. The general analytical procedure and application of reference materials follow the method described in Beinlich et al. (2018; doi:10.1038/s41467-018-03039-9).